(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The sociokultural model of world integrity is developed logic of development of scientific picture of the world is reconstructed as cyclic motion of idea depending on the prevailing factors of space, time and «space–time». The leading role of language is grounded in spiritual development of humanity.